Zagorka. Fenomen (nie)obecny. - Gostomska, Anita (Przekłady Literatur Słowiańskich, 2022)
This article shows the phenomenon of Croatian journalist and writer Marija Jurić Zagorka. Well-known in Croatia and recently very popular not only among her readers but also scholars (especially feminist-oriented), she remains almost completely absent in Poland today despite the fact that her first novel, The Slaves [Roblje], was translated at the very beginning of the 20th century and she herself was commemorated as the first female journalist from Central Europe in the 1930s.